إعداد شخصية الشباب المسلم لمواجهة مشاكل الجنسية في ضوء القرآن الكريم والأحاديث المختارة = Preparation of Muslim youth in facing sexual issues in the light of al-Qur’an & selected hadith - Ahmad, Siti Hawa; Ali, Nurul Badriyah; Ramli, Angraini (Universiti Sultan Zainal Abidin (UniSZA), 2017)
Pre-marital pregnancy, fornication, and free mixing between different genders are among the problems faced by Muslim youth nowadays. This paper aims to discuss the personality preparation guidelines in facing sexual activities based on the Story of Prophet Yusuf in al-Qur’an al-Karim as well as selected prophet’s narration in Hadith. The descriptive analysis shows that Qur’an and selected Hadith prepare four dimensions of guidelines which are: spiritual strength, mental strength, emotional strength as well as physical strength. The findings reveal that in terms of spirituality aspect, Muslim youth should be fully conscious of the existence of Allah and think of the bounty divine given by Allah. In terms of mental strength, Muslim youth must have positive thinking and consider the long term effects in this world and next before engaging themselves in the negative activities. Pertaining to emotional strength, Muslim youth should control their anger, and pertaining to physical strength, they need to keep their body healthy.